Utilization of Undergrowth Floating Houses for Aquaculture: A Case Study of Kuala Bubon Village, Aceh District West - kiswanto kiswanto; wintah wintah; Firman Firdauz (Marine Kreatif, 2026)
Floating houses have become a unique attraction in Kuala Bubon Village, Samatiga Subdistrict, West Aceh Regency. Following the tsunami, the fishing community in Kuala Bubon Village received housing assistance in the form of houses built on water, often referred to as floating houses. These floating houses present both a challenge and an opportunity for use in freshwater fish farming.  Utilizing the space beneath floating houses for freshwater fish farming can provide fishermen with an alternative livelihood beyond open-sea fishing. This study on the use of the space beneath floating houses for fish farming aims to examine the utilization of this space for fish farming, along with its challenges and potential. The study was conducted through the 2026 Student Impact Program using a qualitative descriptive method, involving interviews and observations during the implementation of fish farming assistance to the Kuala Bubon fisherfolk partner group, who utilize the spaces beneath floating houses for fish farming. The spaces beneath floating houses can be productively utilized for the cultivation of gurami, tilapia, and catfish using the fixed-net cage system. Challenges in utilizing these spaces for fish farming include the potential for heavy metal bioaccumulation, difficulties in implementing water quality management, and lower productivity compared to artificial ponds. Fish farming under the house is recommended for gurami, tilapia, and catfish, considering consumer safety regarding heavy metal bioaccumulation.